STUDY OF MARINE ECOTOURISM POTENTIAL BINASI BEACH CENTRAL TAPANULI REGENCYNORTH SUMATERA PROVINCE - Muhammad Alam Mulia Hasibuan; Joko Samiaji; Dessy Yoswaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The study was conducted in February 2019 in Binasi Beach, Central Tapanuli Regency, North Sumatera Province. The research aims to find out the main marine ecotourism object owned by Binasi Beach and its potential development strategy. The method used was a survey method and the determination of station points by purposive sampling. The results showed that the main attraction of Binasi Beach is the scenic beach scenery with clear waters, white and clean sand, and the phenomenon of the sunset. The value of the Tourism Suitability Index ranged from 85.26%–91.67%.The Binasi Beach Strength-Opportunity (SO) Strategy is the development of marine tourism with the concept of ecotourism and creating jobs and preserving nature. The Weakness-Opportunity (WO) strategy consists of increasing the promotion of national and international scale tourism, the development of tourist support facilities, and improving the quality of human resources through education and training. The Strength-Threat Strategy (ST) consists of drafting detailed zoning and regulation of the development of marine ecotourism potential and involving government agencies, the private sector, environmental NGOs, the community, and volunteers to oversee the activities of developing marine ecotourism potential. The Weakness-Threat (WT) strategy consists of counseling about the importance of environmental preservation, pollution hazards, and natural disaster management and the development of creative industries (souvenirs and special foods) as additional attractions for tourists.Keywords:Potential, Marine Ecotourism, SWOT Analysis, BinasiBeach